Does Altitude Affect The Physical Literacy Outcomes of Elementary School Students in Lowland and Highland Areas? - Septian, Immanuel Berli; S, Adi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is motivated by the limited physical literacy in Indonesia, whereas physical literacy can enhance individuals' quality of life. The objective of this study is to compare physical literacy in elementary schools located in lowland areas with those in highland areas and to provide new references related to physical literacy research in Indonesia. The data collection method used interviews for observation and the TLJSD-DKF instrument, physical literacy in elementary schools, and questionnaires. Data analysis in this study used Microsoft Excel and SPSS version 26 for normality tests, homogeneity tests, and t-tests. The results of the data analysis in the hypothesis testing of physical literacy assessment for both male and female students showed significant values greater than the alpha value of 0.05, namely 0.234 > 0.05 for males and 0.362 > 0.05 for females. Then, in the hypothesis testing of knowledge and understanding, it showed a significant value of 0.094, greater than the alpha value of 0.05, whereas in the hypothesis testing of motivation and self-confidence, it showed a significant value of 0.008 less than the alpha value of 0.05.